Predictors of menstrual health management among the high school adolescent girls - Dogra, Ekta; Kumar, Suresh; Guleri, Namrata; Sharma, Ekta (Indian Journal of Community Health, 2024)
Background: Adolescence (10-19 years) is an essential human developmental stage, during which physical, sexual, psychological, and social development occurs Objectives: To estimate the knowledge and attitude regarding menstruation health as well as its determinants among school going adolescent girls. Methods: A questionnaire based cross-sectional study was conducted among school going adolescent girls. In addition to descriptive analysis, bi-variate analysis was also done to find out the association between various predictors of knowledge and attitudes of the study population. Results: Majority of the adolescent girls preferred mother (75.6%) as a source of information regarding puberty related issue with 86.2% of them using health related sanitary pad as one of the methods for menstrual hygiene. Conclusion: Proper menstrual hygiene practices which could be imparted through appropriate interventions at earlier stages of life can prevent the girls and women from suffering reproductive morbidities.